2019
DOI: 10.4038/tar.v30i3.8317
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary evaluation of probiotic potential of yeasts isolated from bovine milk and curd of Sri Lanka

Abstract: There has been mounting interest in the health benefits associated with live microorganisms commonly known as probiotics. Many probiotic bacterial species have been identified. However, the potential of yeasts as a source of probiotics has not been well explored. The present study was carried out to screen and identify potential probiotic yeasts from selected dairy sources available in Sri Lanka. Yeasts from raw bovine milk and curd were isolated, purified, selected and phenotypically characterized by performi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Generally, most of the strains retained their viability at low pH, with the exception of K2-6, M4-5, M4-6, and M8-1 (Şanlidere Aloğlu et al, 2016). Rajawardana et al (2019) reported that yeast strains could grow and survive for up to 5 h at a range of pH values (YPD broth adjusted to pH 1.5, 3.0, and 9). Those authors found that the viability of several strains of yeast decreased at pH 1.5 and increased at pH 9 over 5 h. Their results suggested that the yeast strains survive in the extreme acidic and alkaline conditions encountered in the stomach and intestines.…”
Section: Acid Tolerance Of Yeastsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, most of the strains retained their viability at low pH, with the exception of K2-6, M4-5, M4-6, and M8-1 (Şanlidere Aloğlu et al, 2016). Rajawardana et al (2019) reported that yeast strains could grow and survive for up to 5 h at a range of pH values (YPD broth adjusted to pH 1.5, 3.0, and 9). Those authors found that the viability of several strains of yeast decreased at pH 1.5 and increased at pH 9 over 5 h. Their results suggested that the yeast strains survive in the extreme acidic and alkaline conditions encountered in the stomach and intestines.…”
Section: Acid Tolerance Of Yeastsmentioning
confidence: 99%
“…In addition, the commercial strain and P. kudriavzevii exhibited similar results regarding tolerance to gastric juice. Rajawardana et al (2019) tested the tolerance of yeast to simulated gastric enzymes (YPD broth, pepsin, and pancreatin separately, with 2 pH levels: 2 and 8). They found that, at pH 8, the isolates showed steady growth and survival in gastric and pancreatic juices, whereas at pH 2, the isolates exhibited a slow growth.…”
Section: Acid Tolerance Of Yeastsmentioning
confidence: 99%